2010
DOI: 10.1002/ajp.20900
|View full text |Cite
|
Sign up to set email alerts
|

Resource partitioning in sympatric langurs and macaques in tropical rainforests of the central Western Ghats, south India

Abstract: In a competitive sympatric association, coexisting species may try to reduce interspecific interactions as well as competition for similar resources by several ecological and behavioral practices. We studied resource utilization of three sympatric primate species namely, lion-tailed macaques (Macaca silenus), bonnet macaques (M. radiata) and Hanuman langurs (Semnopithecus entellus) in a tropical rainforest of the central Western Ghats, south India. We studied resource use, tree-height use, foraging height, sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…In a competitive sympatric association, coexisting species may try to reduce interspecific interactions as well as competition for similar resources by several ecological and behavioral practices. Primate species used different heights for foraging, and the two macaque species searched different substrates when foraging on animal prey (Singh et al 2011). Identical vertical stratification, niche breadth and overlap among Rhesus Monkey, Capped Langur and the Hoolock Gibbon have been observed during the present study, wherein it has been observed that Rhesus Monkey used a lower niche and the Hoolock Gibbon prefer a niche that occupies the middle canopy, whereas the capped langur explored both the middle and upper niches.…”
Section: Discussionsupporting
confidence: 68%
“…In a competitive sympatric association, coexisting species may try to reduce interspecific interactions as well as competition for similar resources by several ecological and behavioral practices. Primate species used different heights for foraging, and the two macaque species searched different substrates when foraging on animal prey (Singh et al 2011). Identical vertical stratification, niche breadth and overlap among Rhesus Monkey, Capped Langur and the Hoolock Gibbon have been observed during the present study, wherein it has been observed that Rhesus Monkey used a lower niche and the Hoolock Gibbon prefer a niche that occupies the middle canopy, whereas the capped langur explored both the middle and upper niches.…”
Section: Discussionsupporting
confidence: 68%
“…In order to get a better understanding of the dietary diversity of these primates, we selected a region of the Western Ghats where lion-tailed macaques, bonnet macaques and Hanuman langurs are sympatric in the rain forests. In an earlier study [Singh et al, 2011], we reported that, in this region of the Western Ghats, the food niche overlap between the three primate species over the year was very small, except between bonnet macaques and lion-tailed macaques for a few months when resources were abundant. Since the availability of leaves is much higher than that of fruits, we expected that the primarily folivorous langurs would use a larger number of resources than the primarily frugivorous macaques.…”
Section: Introductionmentioning
confidence: 78%
“…In other words, all the primate species are mostly dependent on those plant species which are abundantly available in that region. The monthly productivity sampling denoted the presence of different resource parts of those major plant species [Singh et al, 2011]. Although some of the resources are very seasonal (like fruits of Garcinia gummigutta in the wet season or Holigarna grahamii in the dry season), the consumption frequency of those resources was very high.…”
Section: Discussionmentioning
confidence: 99%
“…The major plant species and their parts used by Hanuman langurs are given in table 1 . Fruiting trees were abundant in this area [Singh et al, 2011]. The present study group occupied an area around Gerusoppa KPC quarters.…”
Section: Study Sitementioning
confidence: 81%
“…The study area is lowaltitude degraded coastal evergreen rain forest in the Western Ghats of north Karnataka in Uttara Kannada District. The forest comprises mainly Dipterocarpus-Holigarna-Persia species with an average altitude of 650 m [Singh et al, 2011] with an average annual precipitation of 4,200 mm and a relatively high humidity of 95%. The major plant species and their parts used by Hanuman langurs are given in table 1 .…”
Section: Study Sitementioning
confidence: 99%